Predictors for health facility delivery in Busia district of Uganda: a cross sectional study - Anyait Agnes; Mukanga David; Oundo George; Nuwaha Fred (BMC, 2012)
Abstract Background Among the factors contributing to the high maternal morbidity and mortality in Uganda is the high proportion of pregnant women who do not deliver under supervision in health facilities. This study aimed to identify the independent predictors of health facility delivery in Busia a rural district in Uganda with a view of suggesting measures for remedial action. Methods In a cross sectional survey, 500 women who had a delivery in the past two years (from November 16 2005 to November 15 2007) were interviewed regarding place of delivery, demographic characteristics, reproductive history, attendance for antenatal care, accessibility of health services, preferred delivery positions, preference for disposal of placenta and mother's autonomy in decision making. In addition the household socio economic status was assessed. The independent predictors of health facility delivery were identified by comparing women who delivered in health facilities to those who did not, using bivariate and binary logistic regression analysis. Results Eight independent predictors that favoured delivery in a health facility include: being of high socio-economic status (adjusted odds ratio [AOR] 2.8 95% Confidence interval [95% CI]1.2-6.3), previous difficult delivery (AOR 4.2, 95% CI 3.0-8.0), parity less than four (AOR 2.9, 95% CI 1.6-5.6), preference of supine position for second stage of labour (AOR 5.9, 95% CI 3.5-11.1) preferring health workers to dispose the placenta (AOR 12.1, 95% CI 4.3-34.1), not having difficulty with transport (AOR 2.0, 95% CI 1.2-3.5), being autonomous in decision to attend antenatal care (AOR 1.9, 95% CI 1.1-3.4) and depending on other people (e.g. spouse) in making a decision of where to deliver from (AOR 2.4, 95% CI 1.4-4.6). A model with these 8 variables had an overall correct classification of 81.4% (chi square = 230.3, P < 0.001). Conclusions These data suggest that in order to increase health facility deliveries there is need for reaching women of low social economic status and of higher parity with suitable interventions aimed at reducing barriers that make women less likely to deliver in health units such as ensuring availability of transport and involving spouses in the birth plan.